Prevalencia de parásitos gastrointestinales en cerdos de traspatio en el Cantón Guaranda, Provincia Bolívar. - Díaz Sánchez, Katherinne Sthefanny (2023)
This study was conducted in the Gabriel Ignacio de Veintimilla parish of Guaranda canton, aiming to determine the prevalence of gastrointestinal parasites in backyard pigs. A total of 201 fecal samples were analyzed using the saline flotation technique, and the eggs per gram of feces were quantified using the McMaster technique. Larval culture was performed to identify the parasitic species present in the pigs. The results revealed the presence of various parasites, with the most common being Strongyloides spp. (66.67%), Trichuris spp. (53.23%), Ascaris suum (53.25%), Balantidium spp. (38.81%), Globocephalus spp. (30.35%), and Hyostrongylus spp. (27.86%). Interestingly, despite the owners deworming their pigs, a high prevalence of parasites was found in the studied pigs. Furthermore, it was observed that 46.77% of the pig owners were unaware of the type of antiparasitic used, and 31.84% of the owners did not carry out any deworming for their pigs. This suggests the possibility of resistance to the antiparasitics used or the need for a more effective and personalized deworming strategy based on regular monitoring and coproparasitological examinations to identify the specific parasites present on each farm. Therefore, it is necessary to implement more effective deworming strategies based on regular monitoring and coproparasitological examinations to select the most suitable antiparasitic and achieve more efficient control of parasite presence in pig farms.